Dermatopatias em cães: Revisão de 257 casos - Cardoso, Mauro José Lahm; Machado, Luiz Henrique Araújo [UNESP]; Melussi, Maíra; Zamarian, Thaís Pitelli; Carnielli, Cássia Maria; Júnior, José Carlos Melo Ferreira (My University, 2011)
The purpose of this study was to collect data on skin diseases in dogs evaluated at the Veterinary Hospital of the Northern Parana State University (UENP), in Bandeirantes, Parana, Brazil. Dermatological conditions amounted to 31.38% of all consultations in dogs, and the most common skin conditions observed were, from the most to the least common: bacterial, parasitic, fungal, immune, and keratinization disorders; general skin diseases and psychogenic conditions. The highest scoring diseases, in number of occurrences were, in descending order: Superficial folliculitis, demodicidosis, dermatophytosis, bacterial otitis, deep folliculitis, dry dekeratinization, allergic dermatitis caused by flea bites, fungal ear infections, scabies, impetigo, malassezia dermatitis, parasitical otitis, pad dermatitis, and atopic dermatitis.
Skin diseases in dogs: A review of 257 cases
Keywords: Bacterial; Dogs; Fungal; Immune; Parasitic; Skin diseases